Effect of Post-Aging on Laser-Boronized Surface of 18Ni-300 Maraging Steel with Hypoeutectic Structure - Jelena Škamat; Olegas Černašėjus; Kęstutis Bučelis; Oleksandr Kapustynskyi (Lubricants)
Laser-boronized parts manufactured by a selective laser melting process from 18Ni to 300 maraging steel are investigated in this study. Two main issues are addressed, namely (i) the possibility to restore the hardness of the heat-affected zone (HAZ) formed during laser processing and (ii) the effect of re-aging on the hardness and wear resistance of the laser-boronized layer with a hypoeutectic structure. Optical microscopy, scanning electron microscopy, energy-dispersive spectroscopy, X-ray diffraction analysis, microhardness measurements, the “ball-on-plate” dry sliding test, and the two-body dry abrasive wear test were employed to answer the questions. The results confirmed that HAZ is formed with the dissolution of intermetallides formed before and undergo full (near the molten pool) or partial (at some distance from the molten pool) iron–base matrix recrystallization. The hardness of HAZ (350–550 HK0.05) has been restored after re-aging to the 550–600 HK0.05 level. Moreover, a certain positive effect of re-aging on the laser-boronized layer with a hardness of ~470–750 HK0.2 is established, associated with structural transformations induced by aging in the iron-based solid solution phase. The hardness increased by ~9–25%. The wear resistance of the hardest boronized samples (~750 HK0.2) under dry sliding and dry abrasive wear conditions was ~5.8 times and 3.7 times higher than that of the aged control sample, while re-aging provided further improvement of these characteristics. The presented results provide insights into the effectiveness of laser-boronized layers having a hypoeutectic structure in terms of increasing the wear resistance of maraging steel.